Spatio-temporal patterns of the oceanic conditions and nearshore marine community in the Mid-Atlantic Bight (New Jersey, USA) - Levesque,Juan C. (PeerJ, 2019)
Oceanic environmental conditions influence, shape, and control the geographical range, spatial distribution, abundance, and size composition of marine fauna. Water temperature, salinity, dissolved oxygen, depth, and sediment type influence select fish life-history characteristics and community structure. Marine communities are vulnerable to major changes in environmental conditions, but the response and severity depends on various biological or ecological factors, such as resilience to stress or adaptation. Researchers around the world have predicted and documented numerous alterations in fish communities caused by ongoing significant physicochemical shifts associated with natural and potentially unnatural sources, but published studies describing the historical conditions are lacking for most regions around the world, including the coastal waters off New Jersey. Given the need to understand these processes, a multifaceted investigation was undertaken to describe, evaluate, and compare the oceanic conditions and nearshore marine fauna community off New Jersey during 1988 through 2015. Findings showed the oceanic conditions varied over time and space. Mean surface water temperature increased significantly about 0.6 °C per decade, mean salinity decreased about 1.3 psu per decade, and dissolved oxygen increased 0.09 mg/l per decade. Over 20.4 million fish and invertebrates (1,338.3 mt) representing 214 (water temperature preference classified) species (not including unidentified species) were collected within 15 strata (areas: 12−26) off the coast of New Jersey from 1988 to 2015. Three marine fauna water temperature preference groups (coldwater-adapted, warmwater-adapted, and subtropic-adapted) were identified in the study area. The main coldwater-adapted species collected were longfin squid (Loligo pealei) (n = 2, 225, 975), Atlantic herring (Clupea harengus) (n = 544, 032), and little skate (Leucoraja erinacea) (n = 316, 356), while Atlantic butterfish (Peprilus triacanthus) (n = 2, 873, 138), scup (Stenotomus chrysops) (n = 1, 318, 569), and northern searobin (Prionotus carolinus) (n = 503, 230) represented the warmwater-adapted group. Bay anchovy (Anchoa mitchilli) (n = 9, 227, 960), striped anchovy (Anchoa hepsetus) (n = 245, 214), and Atlantic moonfish (Vomer setapinnis) (n = 38, 691) denoted the subtropic-adapted group. Subtropic-adapted species were the most abundant and coldwater-adapted were the least abundant water temperature preference group. The estimated abundance of coldwater-adapted species declined, warmwater-adapted species slightly increased, and subtropic-adapted species decreased with time, which suggest the environmental conditions are influencing and thereby shifting the marine community.
Keywords: Climate variability; Community dynamics; Ecosystem science; Experimental design; Fisheries independent monitoring; Fisheries and fish science; Population dynamics